STUDI EVALUASI PERENCANAAN JARINGAN IRIGASI SALURAN SEKUNDER BLT.1 BLS.1 BLS.2 BLS 3 BLS.4 DI DESA LODOYO KECAMATAN SUTOJAYAN KABUPATEN BLITAR PROVINSI JAWA TIMUR - Ahmad Taufik; Eko Noerhayati; Bambang Suprapto (Jurnal Rekayasa Sipil, 2020)
The Lodoyo Irrigation Area is one of the irrigation areas in Blitar Regency which has a standard rice field area of 1230.7 hectares. In Lodoyo Village there are paddy fields whose irrigation canals have suffered a lot of damage resulting in decreased performance in water distribution. The irrigation network in the Lodoyo irrigation area is a fairly fertile area, but it needs attention in terms of improvement and physical facilities in its irrigation. The purpose of this study was to determine the existing conditions in the network channel, determine the mainstay discharge, determine the level of water efficiency in the channel, determine the dimensions of the planned network channel in order to accommodate rainwater. This research was conducted in Lodoyo area, Sutojoyan District, Blitar Regency, East Java Province. In this study the plan discharge is used to plan the irrigation network channel. Channel 1 is unable to load and drain the water flow that will be flowed so a re-planning is needed because the existing channel discharge is 11,152 m3/sec while the planned discharge is 24,140 m3 / sec, with square channel dimension planning of, channel base width (B) = 3.80 m , water level (h) = 1.90 m, a flowrate (Q) of 24,140 m3 / s is obtained. With the evaluation of the channel dimension plan, the network channel is able to accommodate the flow of water that will flow through the rice fields so that there is no flooding.Keywords: Irrigation Channel Planning, DI Lodoyo, Blitar Regency